Giant cavernoma mimicking a right frontal tumor - Barry, Louncény Fatoumata; Sy, El hadji Cheikh Ndiaye; Faye, Mohameth; Ba, Momar Code (Nepal Journal of Neuroscience, 2021)
Cavernomas account for 9 to 16% of cerebrovascular malformations with a prevalence of 0.5% in the general population. We report a case of a large frontal cavernoma mimicking a frontal tumor and revealed by epileptic seizures. We report a 40-year-old man, without any particular history, received in consultation for tonic-clonic generalized convulsive seizures evolving for 5 years with a normal clinical examination on admission. Cerebral CT scan revealed a large right frontal lesion suggestive of a brain tumor, requiring surgical removal after persistent seizures despite dual antiepileptic therapy. The evolution was favorable at one year with the total cessation of the convulsive seizures without neurological after-effects. In conclusion, giant brain cavernomas are rare lesions and may be mistaken for a brain tumor.